2020
DOI: 10.3389/fpls.2020.00886
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acids Released in Maize Rhizosphere During Maize-Soybean Intercropping Inhibit Phytophthora Blight of Soybean

Abstract: Interspecies interactions play a key role in soil-borne disease suppression in intercropping systems. However, there are limited data on the underlying mechanisms of soil-borne Phytophthora disease suppression. Here, a field experiment confirmed the effects of maize and soybean intercropping on Phytophthora blight of soybean caused by Phytophthora sojae. Experimentally, the roots and root exudates of maize were found to attract P. sojae zoospores and inhibit their motility and the germination of cystospores. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 71 publications
(102 reference statements)
1
26
0
Order By: Relevance
“…The inhibition effect was 21.5-75.7% and 48.7-100% at the concentrations of 10 mM and 20 mM, respectively [60]. Meanwhile, PAs have been shown to have antifungal effects, inhibitory effects on reducing growth of weed species and aid in the formation and stabilization of aggregates under appropriate concentrations [61][62][63]. The research results of Hou et al showed that B. cinerea mycelial growth and spore generation decreased by 86.18% and 69.10%, respectively, following 0.2 g/L PAs treatment [64].…”
Section: Allelochemicalsmentioning
confidence: 99%
“…The inhibition effect was 21.5-75.7% and 48.7-100% at the concentrations of 10 mM and 20 mM, respectively [60]. Meanwhile, PAs have been shown to have antifungal effects, inhibitory effects on reducing growth of weed species and aid in the formation and stabilization of aggregates under appropriate concentrations [61][62][63]. The research results of Hou et al showed that B. cinerea mycelial growth and spore generation decreased by 86.18% and 69.10%, respectively, following 0.2 g/L PAs treatment [64].…”
Section: Allelochemicalsmentioning
confidence: 99%
“…They are involved in attracting or repulsing beneficial and pathogenic microorganisms ( Fig. 2 C) [57] , [58] , [59] . Investigations addressing how and which rhizospheric compounds direct zoospore chemotaxis toward roots have resulted in the identification of stimuli among root exudates.…”
Section: The Plant Environment: the Rhizospherementioning
confidence: 99%
“…Ferulic acid is an abundant phenolic acid attached to plant walls and its abundance in maize is at least ten times more than in other cereals (Bento-Silva et al, 2018). Ferulic acid is released by corn roots (Zhang et al, 2020). In bean, coumaric acid and 4-hydroxybenzoate may be preferentially used by Ch24-10 according to the level expression of pobA gene and pca operon.…”
Section: Discussionmentioning
confidence: 99%
“…Ch24-10 metabolic processes induced by milpa exudates are denoted by a red asterisk. The information used here was obtained from transcriptome data in the presence of beans (Supplementary Table 1), maize (Supplementary Table 2), and milpa (Supplementary Table 3) and from data about chemical composition of exudates reported in the literature (Bolaños-Vásquez and Werner, 1997; Carvalhais et al, 2011;Fan et al, 2012;Tawaraya et al, 2014;Zhang et al, 2020). flagellar motor, hook and basal complex, and for the biosynthesis of flagellin were found expressed in all transcriptomes.…”
Section: Rhizobial Genes Induced By Bean or Maize Monoculturesmentioning
confidence: 99%